Gravity in Action - Kothari, L.S. (SCHOOL SCIENCE, 2013)
ou might have wondered why objects when released from a certain height fall down on the ground. When you throw a ball up it does not continue going up, but soon comes to a halt at a certain height and then begins to fall. As it falls it gains speed. If we release two bodies of different masses from a certain height, say the roof of a house, will they reach the ground at the same time or at different times? This question is not at all easy to answer. If you drop a piece of paper and glass marble from a certain height, the marble will hit the ground much before the slip of paper reaches there. Even if we take objects of similar shape the answer is not easy. ou might have noticed that larger rain-drops fall much faster than smaller ones – though all drops are spherical in shape. Even if we take two identical spheres, say one made of lead and the other of wood, can one say that they will fall together when released from a height simultaneously. The great Greek philosopher Aristotle (384 -322 B.C.) firmly believed that heavier objects fall faster than lighter objects of identical shape. No one questioned his judgement for many centuries and probably no one ever tried to verify whether what Aristotle said was correct.